Involvement of a cis-element that binds an H2TF-1/NF kappa B like factor(s) in the virus-induced interferon-beta gene expression. - Fujita, T (1989)
Interferon-beta (IFN-beta) gene is transcriptionally activated following virus infection of various cell types such as fibroblasts. In the previous studies, regulatory DNA sequences that mediate the virus-induced transcriptional activation have been identified within the 5'-flanking region (up to around -117 respect to the CAP site) of the human IFN-beta gene. The sequences contain binding sites (-100 to -61) for a transcriptional activator, IRF-1, the gene of which is also virus-inducible. In the present study, we focused on an additional cis-element, located between the IRF-1 binding sites and TATA box. Interestingly, the element coincides with the previously identified elements for the transcription factors H2TF-1 and NF kappa B. The element, when tandemly repeated, functions in activating the distal gene expression in either constitutive or virus-inducible manner depending on the cell type. The results suggest the importance of cooperation between IRF-1 and H2TF-1/NF kappa B-like factor in the maximal IFN-beta gene induction.